Bridging Myositis Ossificans After Supracondylar Humeral Fracture in a Child: A Case Report - Chen, Jiayuan; Li, Qilin; Liu, Tianjing; Jia, Guoqiang; Wang, Enbo (Frontiers in Pediatrics, 2021)
Abstract Background: Myositis ossificans is an uncommon complication of trauma and surgery, defined as ossifying changes in a non-osseous tissue such as muscles. It happens after tissue injury, with or without fractures. When myositis ossificans occurs around a joint, it can cause ankylosis, leading to complete dysfunction of the joint. Though it has been described in most parts of the body, bridging myositis ossificans involving the elbow joint were scarcely reported. Case presentation: we report a severe case of myositis ossificans after a supracondylar humerus fracture in a 9-year-old child. In this case a palpable painless mass appeared following the fracture and surgical trauma. Ultrasound or X-ray is of significant diagnostic value. The brachialis was completely ossified and formed a bony bridge around the elbow, causing complete ankylosis. The bone mass was surgically removed through a bilateral less-invasive approach with less surgical trauma nine months after initial presentation. we applied bone wax to the fresh bone wounds to prevent the formation of hematocele. Indomethacin, a non-steroidal anti-inflammatory drug, was administered after the operation to suppress bone proliferation in our case. Our patient had the best possible functional status and no recurrence at two years’ follow-up. Conclusion: elbow myositis ossificans in children may mainly affects the brachialis. A bilateral less-invasive approach is sufficient to remove the bone mass with less surgical trauma. This case also provides a new reference for the treatment of myositis ossificans after the elbow injuries.